Relevansi Pemikiran Hukum Imam Malik Dengan Konteks Indonesia Tentang Pernikahan Beda Agama - Kusnadi Kusnadi (LPPM STIS Hidayatullah, 2023)
This article aims to explain the legal product of Imam Malik in a sociological perspective and its correlation with the Indonesian context. Imam Malik studied in the city of Medina. The legal issues in Medina were not as complex as those in Iraq. In determining the law, he first based his ijtihad on the zahir texts and used more hadiths. Imam Malik used this method because he was influenced by the social and political conditions of the city of Medina. The Ijtihad method used by Imam Malik is the Koran, As-Sunnah, al-Ijma', al-Qiyas, amalu ahl al- Madinah, qaul as-Shahabah, istihsan, al-Maslahah al-Mursalah, Muratul Ikhtilaf, syadd az- Zariah, syar'u man qablanah. As for the legal product of Imam Malik related to the issue of interfaith marriage, Muslim men marrying women of the Ahlul Kitab who adhere to Judaism and Christianity is makruh, because they eat things that are forbidden, such as pork and drinking intoxicants, and children who are born sometimes follow their mother's religion. As for its relevance to the legal context in Indonesia, interfaith marriages are more prohibited, except for Muslim men and women of the Ahlul Kitab by Imam Malik, who are considered makruh. This decision is relevant to KHI provisions, MUI decisions, and Muhammadiyah Tarjih Council decisions.